Cerebral and skeletal muscle tissue oxygenation during exercise challenge in children and young adults with sickle cell anaemia. (26th July 2021) - Barriteau, Christina M.; Chiu, Abraham; Rodeghier, Mark; Liem, Robert I.
Summary: We used near‐infrared spectroscopy to examine tissue oxygenation (StO2) during exercise in 17 children and young adults with sickle cell anaemia (SCA) and 13 controls. Patients had lower cerebral StO2 at all exercise stages and demonstrated significantly greater decreases in cerebral StO2 later during exercise. Quadriceps StO2 increased similarly in patients and controls during early exercise, but decreases from baseline were greater in patients during later exercise. At similar workloads, patients demonstrated lower cerebral StO2 (69·2 ± 6·6 vs. 79·5 ± 5·3%, P  < 0·001) and trended towards lower quadriceps StO2 (67·7 ± 9·0 vs. 73·2 ± 7·9%, P  = 0·09) . Further studies of tissue oxygenation during exercise in SCA are warranted.